The use of social media in promoting selected underrated restaurants along P. Noval: a new strategy that will affect consumer buying decision - Guamos,Kim Dominique D. Lopez, Mary Grace M. Narciso, Maybel C. Quitaleg, Elyza Marie C. Untalan, David Paul T. , and Valliente, Sharmaine Y. 4 0 16; 5 (2016)
u
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila 2016.
Keywords: 2 -- 0; 6; 20; 20; 2